Effect of NiO and ZnO Sintering Aids on Sinterability and Electrochemical Performance of BCZY Electrolyte - Saheli Biswas; Sareh Vafakhah; Gurpreet Kaur; Aaron Seeber; Sarbjit Giddey (Ceramics)
Proton-conducting ceramics have gained significant attention in various applications. Yttrium-doped barium cerium zirconate (BaCexZr1−x−yYyO3–δ) is the state-of-the-art proton-conducting electrolyte but poses a major challenge because of its high sintering temperature. Sintering aids have been found to substantially reduce the sintering temperature of BaCexZr1−x−yYyO3–δ. This work evaluates, for the first time, the impact of NiO and ZnO addition in three different loadings (1, 3, 5 mol%), via wet mechanical mixing, on the sintering and electrical properties of a low cerium-containing composition, BaCe0.2Zr0.7Y0.1O3–δ (BCZY). The sintering temperature remarkably dropped from 1600 °C (for pure BCZY) to 1350 °C (for NiOBCZY and ZnOBCZY) while achieving > 95% densification. In general, ZnO gave higher densification than NiO, the highest being 99% for 5 mol% ZnOBCZY. Dilatometric studies revealed that ZnOBCZY attained complete shrinkage at temperatures lower than NiOBCZY. Up to 650 °C, ZnO showed higher conductivity compared to NiO for the same loading, mostly due to a higher extent of Zn incorporation inside the BCZY lattice as seen from the BCZY peak shift to a lower Bragg’s angle in X-ray diffractograms, and the bigger grain sizes of ZnO samples compared to NiO captured in scanning electron microscopy. At any temperature, the variation in conductivity as a function of sintering aid concentration followed the orders 1 mol% > 3 mol% > 5 mol% (for ZnO) and 1 mol% < 3 mol%~5 mol% (for NiO). This difference in conductivity trends has been attributed to the fact that Zn fully dissolves into the BCZY matrix, unlike NiO which mostly accumulates at the grain boundaries. At 600 °C, 1 mol% ZnOBCZY showed the highest conductivity of 5.02 mS/cm, which is, by far, higher than what has been reported in the literature for a Ce/Zr molar ratio <1. This makes ZnO a better sintering aid than NiO (in the range of 1 to 5 mol% addition) in terms of higher densification at a sintering temperature as low as 1350 °C, and higher conductivity.